INOVASI PRODUK SELANG UNTUK MENINGKATKAN EKONOMI UMKM DESA GUNUNG MALANG - Mursyidah, Azizah; Kulsum, Umi; Tuzahro, Siti Fatimah (LPPM Universitas Al Muslim, 2024)
This community service activity examines the potential of natural resources in Gunung Malang Village, Bogor Regency and its development efforts. This village has a variety of natural resources, including land, water and agricultural products, and its location on the equator supports the growth of tropical rainforests. The innovation approach in Gunung Malang Village is the development of SELANG (Selai Buah Pala Gunung Malang/Gunung Malang Nutmeg Jam) as an innovative product. SELANG was chosen based on a network of ideas and consideration of the abundant availability of nutmeg raw materials. Making SELANG involves the process of manufacturing, branding, packaging with digital business marketing. This innovation is directed at increasing the income of village communities. The method for implementing community service activities were a participatory approach for adults through lectures, training and assistance in its establishment and management, and inviting participants to be creative and innovative in producing products. The results of the activities showed the similarity of ideas in the village community to create souvenirs typical of Mount Malang which focus on SELANG products. Thus, SELANG product innovation helps the MSME community of Gunung Malang Village to improve their welfare, through product manufacturing and packaging, as well as digital marketing. This can be seen by an increase in partner income so that the MSME community is independent and prosperous.